2021
DOI: 10.3892/ijmm.2021.4913
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non‑coding RNA DLEU2 suppresses idiopathic pulmonary fibrosis by regulating the microRNA‑369‑3p/TRIM2 axis

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most common form of idiopathic interstitial pneumonia with an increasing incidence. In the present study, Genome Expression Omnibus (GEO) datasets (GSE10667, GSE24206 and GSE32537) were applied to identify lncRNA DLEU2 in IPF. Through prediction using starBase, TargetScan, miRTarBase and miRDB, tripartite motif containing 2 (TRIM2) and prostaglandin F2 receptor inhibitor (PTGFRN) were found to be upregulated in IPF. DLEU2 expression, the mRNA expression of TRIM2 and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…The transmembrane Ig superfamily protein PTGFRN was strongly increased in mature scar. This protein was previously shown to be increased in IPF and in bleomycin-induced lung injury ( 59 ). By contrast, the laminin receptor BCAM was decreased in mature scar, consistent with decreased expression of laminin proteins in this region ( 60 ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The transmembrane Ig superfamily protein PTGFRN was strongly increased in mature scar. This protein was previously shown to be increased in IPF and in bleomycin-induced lung injury ( 59 ). By contrast, the laminin receptor BCAM was decreased in mature scar, consistent with decreased expression of laminin proteins in this region ( 60 ).…”
Section: Resultsmentioning
confidence: 84%
“…The transmembrane Ig superfamily protein PTGFRN was strongly increased in mature scar. This protein was previously shown to be increased in both IPF and in bleomycin-induced lung injury [59].…”
Section: The Mature Scar Is Consistent With End-stage Fibrosismentioning
confidence: 83%
“…The transmembrane Ig superfamily protein PTGFRN was strongly increased in IPF mature scar. This protein was previously shown to be increased in both IPF and in bleomycin-induced lung injury [51].…”
Section: The Ipf Mature Scar Is Consistent With End-stage Fibrosismentioning
confidence: 83%
“…Another study reported that LOC541471 is a novel prognostic biomarker for head and neck squamous cell carcinoma [ 38 ]. The leukaemia 2 gene (DLEU2) has been reported to play an important role in a variety of diseases [ 39 , 40 ], especially in tumour diseases, including thyroid cancer, gastric cancer, sarcopenia, and laryngeal squamous cell carcinoma, and has been shown to play a role through the ceRNA mechanism [ 41 – 44 ].…”
Section: Resultsmentioning
confidence: 99%